Radiosynthesis and First Preclinical Evaluation of the Novel 11C-Labeled FAP Inhibitor 11C-FAPI: A Comparative Study of 11C-FAPIs and (68Ga) Ga-DOTA-FAPI-04 in a High–FAP-Expression Mouse Model - Wang, Cheng; Hu, Zhoumi; Ding, Fan; Zhao, Haitao; Du, Fuqiang; Lv, Chun; Li, Lianghua; Huang, Gang; Liu, Jianjun (Frontiers in Chemistry, 2022)
Purpose: 68Ga-labeled fibroblast activation protein inhibitors, such as [68Ga]Ga-DOTA-FAPI-04 and [68Ga]Ga-DOTA-FAPI-46, have been successfully applied in positron emission tomography imaging of various tumor types. To broaden the PET tracers of different positron nuclides for imaging studies of FAP-dependent diseases, we herein report the radiosynthesis and preclinical evaluation of two 11C-labeled FAP inhibitors, 11C-RJ1101 and 11C-RJ1102. Methods: Two phenolic hydroxyl precursors based on a quinoline amide core coupled with a 2-cyanopyrrolidine moiety were coupled with [11C]CH3I to synthesize 11C-RJ1101 and 11C-RJ1102. In vivo small-animal PET and biological distribution studies of 11C-RJ1101 and 11C-RJ1102 compared to [68Ga]Ga-DOTA-FAPI-04 were conducted in nude mice bearing U87MG tumor xenografts at 30, 60, and 90min, respectively. Results: 11C-RJ1101 and 11C-RJ1102 were synthesized in over 15% radiochemical yields, with specific activities of 67 GBq/μmol and 34 GBq/μmol, respectively, at the end of synthesis and radiochemical purities greater than 99%. In U87MG tumor xenograft PET studies, the three tracers experienced higher specific uptake at the tumor site. However, because of significant differences in metabolism and clearance, [68Ga]Ga-DOTA-FAPI-04 experienced high uptake in the kidney, whereas 11C-RJ1101 and 11C-RJ1102 showed high uptake in the liver and intestine. Biodistribution studies revealed significant hepatobiliary excretion of 11C-RJ1101 and 11C-RJ1102. 11C-RJ1102 showed higher specific tumor uptake in U87MG xenografts (1.71 ± 0.08% injected dose per Gram of tissue [ID/g]) than 11C-RJ1101 (1.34 ± 0.10%ID/g) and [68Ga]Ga-DOTA-FAPI-04 (1.29 ± 0.04%ID/g) after 30 min p. i. In orthotopic glioma models, the uptake values were 0.07 ± 0.03% ([68Ga]Ga-DOTA-FAPI-04) and 0.16 ± 0.03% (11C-RJ1102), respectively. Conclusion: 11C-RJ1101 and 11C-RJ1102 are interesting candidates for translation to the clinic, taking advantage of the shorter half-life and physical imaging properties of C-11.